2(x+3)+3x-x=x+16

Simple and best practice solution for 2(x+3)+3x-x=x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)+3x-x=x+16 equation:


Simplifying
2(x + 3) + 3x + -1x = x + 16

Reorder the terms:
2(3 + x) + 3x + -1x = x + 16
(3 * 2 + x * 2) + 3x + -1x = x + 16
(6 + 2x) + 3x + -1x = x + 16

Combine like terms: 2x + 3x = 5x
6 + 5x + -1x = x + 16

Combine like terms: 5x + -1x = 4x
6 + 4x = x + 16

Reorder the terms:
6 + 4x = 16 + x

Solving
6 + 4x = 16 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
6 + 4x + -1x = 16 + x + -1x

Combine like terms: 4x + -1x = 3x
6 + 3x = 16 + x + -1x

Combine like terms: x + -1x = 0
6 + 3x = 16 + 0
6 + 3x = 16

Add '-6' to each side of the equation.
6 + -6 + 3x = 16 + -6

Combine like terms: 6 + -6 = 0
0 + 3x = 16 + -6
3x = 16 + -6

Combine like terms: 16 + -6 = 10
3x = 10

Divide each side by '3'.
x = 3.333333333

Simplifying
x = 3.333333333

See similar equations:

| 10=11+11y | | 5c+13=16 | | 25-7a=28a-4a | | f(2)=3x*2-3x-3 | | 15x-5y+18=20 | | 9q-24=9q-12 | | 6cos^2x-7cosx-3=0 | | 5x+35=135 | | 5.8z-5=4.8z-5 | | 2x+x+3=3x+5 | | -5x-7=9x+15 | | -7-8n=47 | | 5=18 | | 3(-x)+5x=x+9 | | 2(-x)+5x=x+9 | | .1x=-13 | | (12x-30)+3x=180 | | -65-12x+8x=55 | | 2x+3x-40=50 | | ab+bc+ac=-abc | | -19-2x+4x=7 | | 5X-(3)+(-9)=4x-(-7+1) | | ab+bc+ac=1110 | | 2(x+4)+4x-x=2x+20 | | -26-5b=4-7b | | 7+9-3b+20= | | 16-2x=4x | | 6r^2+8r-20=5r^2 | | -91+x+8x=35 | | 2m^2+2m-12=12 | | x=4x+39 | | 9x-76-4x=39 |

Equations solver categories